2012
DOI: 10.1152/ajpcell.00202.2011
|View full text |Cite
|
Sign up to set email alerts
|

Arrestins 2 and 3 differentially regulate ETA and P2Y2 receptor-mediated cell signaling and migration in arterial smooth muscle

Abstract: Morris GE, Nelson CP, Brighton PJ, Standen NB, Challiss RA, Willets JM. Arrestins 2 and 3 differentially regulate ETA and P2Y2 receptor-mediated cell signaling and migration in arterial smooth muscle. Am J Physiol Cell Physiol 302: C723-C734, 2012. First published December 7, 2011; doi:10.1152/ajpcell.00202.2011.-Overstimulation of endothelin type A (ETA) and nucleotide (P2Y) G␣q-coupled receptors in vascular smooth muscle causes vasoconstriction, hypertension, and, eventually, hypertrophy and vascular occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 49 publications
4
34
0
Order By: Relevance
“…Previous in vitro studies identified GRK2 as the key regulator of contractile GPCR-mediated PLC signalling in arterial smooth muscle cells (Cohn et al, 2008;Morris et al, 2012;Morris et al, 2011;Morris et al, 2010), however, the process of interrogating the role that GRK2…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous in vitro studies identified GRK2 as the key regulator of contractile GPCR-mediated PLC signalling in arterial smooth muscle cells (Cohn et al, 2008;Morris et al, 2012;Morris et al, 2011;Morris et al, 2010), however, the process of interrogating the role that GRK2…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown, in smooth muscle cells isolated from 3 rd order rat mesenteric arteries, that GRK2 is the key regulator of phospholipase C/Ca 2+ signalling induced by the vasoconstrictors endothelin and UTP, via the endothelin A (ETA) and purinergic (P2Y2) receptors (Morris et al, 2012;Morris et al, 2011;Morris et al, 2010). GRK2 is also reported to regulate signalling by two further vasoconstrictors, AngII and noradrenaline, through negative regulation of AngII type 1 receptor (AT1) (Kim et al, 2009;Oppermann et al, 1996) and 1D-adrenoceptor (Cohn et al, 2008) signalling.…”
Section: Mol #112524mentioning
confidence: 99%
See 1 more Smart Citation
“…α,β-methylene-ATP inhibited with a halfmaximal concentration of about 0.1 μM the migration of the cells. P2Y receptors including the P2Y 2 , P2Y 6 , and P2Y 12 subtypes mediate the opposite effect-an increase in migration [54][55][56][57][58][59]. Migration facilitated by the activation of P2Y 2 receptors involved the ERK1/2 as well as the arrestin2 pathway [54,58].…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines Purinergic Signaling and Blood Vessels induce upregulation of P2Y 2 receptors on vascular smooth muscle cells, resulting in increased mitogenic responses to UTP and ATP (Hou et al, 2000). Arrestindependent regulation of P2Y 2 receptor-stimulated MAPK signaling is essential for migration of aortic smooth muscle cells, a key event in vascular remodeling (Morris et al, 2012).…”
Section: A Vascular Smooth Musclementioning
confidence: 99%